EFFECT OF INFLATION RATE, NON PERFORMING FINANCING (NPF), AND NUMBER OF BRANCH OFFICES ON MURABAHAH FINANCING AT BANK MUAMALAT INDONESIA - Muhammad Fatchullah El Islami; Tiara Juliana Jaya (AL-IQTISHADIYAH : EKONOMI SYARIAH DAN HUKUM EKONOMI SYARIAH, 2022)
The development of the Islamic economic system was marked when there was a monetary crisis that hit capitalist countries and Indonesia. Bank Muamalat Indonesia became the first Islamic bank in Indonesia as well as being able to exist to survive in the conditions of the monetary crisis. Seeing the consumptive habits of the Indonesian people, murabahah financing products became one of the most popular products for customers. This study will answer whether Inflation, NPF, and the Number of Branch Offices have a significant effect on Murabahah Financing at Bank Muamalat Indonesia. This type of research is a quantitative research using Bank Muamalat's quarterly secondary data, Inflation data from Bank Indonesia, and Number of Branch Office data from Islamic banking statistics for the period 2017-2021. The purpose of this study is to analyze the influence of variable inflation, non-performing financing (NPF), and the number of branch offices on the amount of murabahah financing at Bank Muamalat Indonesia. The study used multiple linear regression analysis methods. The results showed that the inflation variable had a positive effect on murabahah financing, the NPF variable had a negative effect on murabahah financing, while the variable number of branch offices had no effect on murabahah financing Perkembangan sistem ekonomi Islam ditandai ketika terjadi krisis moneter yang melanda negara-negara kapitalis dan Indonesia. Bank Muamalat Indonesia menjadi bank syariah pertama di Indonesia yang mampu bertahan dalam kondisi krisis moneter. Melihat kebiasaan konsumtif masyarakat Indonesia, produk pembiayaan murabahah menjadi salah satu produk yang diminati nasabah. Penelitian ini akan menjawab apakah Inflasi, NPF, dan Jumlah Kantor Cabang berpengaruh signifikan terhadap Pembiayaan Murabahah pada Bank Muamalat Indonesia. Jenis penelitian ini adalah penelitian kuantitatif dengan menggunakan data sekunder triwulan Bank Muamalat, data Inflasi dari Bank Indonesia, dan data Jumlah Kantor Cabang dari statistik perbankan syariah periode 2017-2021. Tujuan penelitian ini adalah untuk menganalisis pengaruh variabel inflasi, non performing financing (NPF), dan jumlah kantor cabang terhadap jumlah pembiayaan murabahah pada Bank Muamalat Indonesia. Penelitian ini menggunakan metode analisis regresi linier berganda. Hasil penelitian menunjukkan bahwa variabel inflasi berpengaruh positif terhadap pembiayaan murabahah, variabel NPF berpengaruh negatif terhadap pembiayaan murabahah, sedangkan variabel jumlah kantor cabang tidak berpengaruh terhadap pembiayaan murabahah.